Effect of Calcium Oxychloride Pre-sowing Treatment to Hasten Germination of Teak (Tectona grandis Linn.f.) Drupes - Masilamani, P.; Dharmalingam, C.; Annadurai, K. (Indian Forester, 2008)
A study was conducted to find out the effect of Calcium oxychloride pre-sowing treatment to improve germination of fresh and ten month-old drupes (fruit with seed) of Teak. The drupes were collected from Top slip seed production area and the drupes were subjected to alternate soaking and drying for 5 days at 12 hrs interval, the 6th day soaking in different concentrations of Calcium oxy chloride (2, 4, 6, 8 and 10%) solution for 12 hrs, compared to water soaking and dry drupes as control. The presoaked drupes were sown in both open and mist chamber condition. Fresh drupes were subjected 2% calcium oxy chloride registered improved germination up to 22% against 4% in control in open condition and 20% and 46% germination in mist chamber with 6% CaOCl2 for fresh and ten month old drupes respectively. Fresh drupes took more number of days for emergence than ten months old drupes, both under open and mist chamber condition.